Multifactor Productivity of Smallholder Yam Farmers in Ebonyi State, Nigeria - Chukwuemeka, Kadurumba; Anayo, Njoku Ignatius; Ogechi, Achi (Agricultura Scientia, 2020)
The study analysed the multifactor productivity among smallholder yam farmers in Ebonyi South, Ebonyi North and Ebonyi Central Agricultural zones of the State. The specific objectives were to determine the socio-economic characteristics of the yam farmers in the study area, to analyse the multifactor productivity and scale of production among smallholder yam farmers, to determine the factors affecting multifactor productivity among smallholder yam farmers and identify constraints of increased yam production in the study area. Two-stage random sampling technique was used to select one hundred and twenty (120) yam farmers from areas of intense yam cultivation in the three zones. Cobb-Douglas production function was used to analyse individual factor productivity and scale of production in yam enterprise. The results revealed that coefficient of farm size, hired labour, household size and planting materials, would reduce multifactor productivity of yam farms by 8.6 %, 1.05 %, 2.2 % and 0.45 %, respectively. The results also showed that 10 % increase in age, income, credit access and experience would increase multifactor productivity of yam farms by 0.071 %, 0.133 %, 0.543 % and 0.139 %, respectively. The R2 values of 0.864 implies that about 86 % of variations in multifactor productivity in yam enterprises are explained by the explanatory variables in the model. The problems identified include inadequate land, finance, high transportation cost, hired labour, pests and diseases, bad infrastructure, network, inadequate storage facilities, etc. The results of the study expressed the need of active policies aimed at intensifying extension services, encouraging farm mechanization and provision of credits at subsidized rate in the state.
Keywords: yam; Dioscorea spp.; multifactor productivity; smallholder; determinants; resources